SHORT-DISTANCE STUDENT-ATHLETES DETERMINATION OF PHYSICAL FITNESS STATE - Boymatov X. X.; Mirzaxmedova D.S. (Proximus Journal Publishing, 2025)
Development of the sport of athletics, for high sports results in the future to achieve, exercise downloads athletes preparation to the level suitable in a wayplanning, the intensity of implementation of the annual workload, the means used,receiving training on the implementation of the methods, short-distance runners exercise downloads in planning athletes individual characteristics to plan and prepare highly qualified athletes, taking into account their integral ready opportunities shaping according to industry specialists by enough studied
Keywords: training processes; optimization; development